Numerical data processing from a laser flash experiment on thin graphite layer - Stryczniewicz, Wit; Panas, Andrzej J. (Computer Assisted Methods in Engineering and Science; Vol 22 No 3 (2015), 2017)
In this paper, the methodology for determination of the out-of-plane thermal diffusivity (TD) of a thin graphite layer deposited onto a substrate of known properties is presented. The developed methodology resulted in combined experimental-numerical procedure enabling investigation of the properties of thin layer deposits. The procedure involves the experimental data acquisition during the laser flash tests, and next the numerical processing of the collected data using the heat conduction problem solution and the nonlinear least square parameter identification approach. Two last steps produce a certain inverse heat conduction problem that is formulated and numerically solved for a three-layer specimen. The procedure has been successfully tested while processing the real experimental data from investigation of flake graphite layers. This proved the effectiveness of the methodology in providing quantitative data on the TD of thin layers of relatively poor conductors deposited onto a highly conductive substrate.